A generic method for assessment of inhomogeneous wave load effects of very long floating bridges. (May 2022) - Cui, Minghao; Cheng, Zhengshun; Moan, Torgeir
Abstract: Floating bridges are promising infrastructures used to cross wide and deep fjords. During the design of floating bridges, the wave field is usually assumed long-crested and homogeneous. However, the real wave field in fjords is short-crested and inhomogeneous due to the complicated topography. To evaluate the uncertainties implied by the homogeneous assumption, a generic method is proposed in this study for the assessment of inhomogeneous wave load effects of very long floating bridges. The inhomogeneous wave field is represented by the long-term variation and correlation of wave spectral parameters at the location of each pontoon and by coherence functions of wave elevations between pontoons. The correlated and inhomogeneous wave field is simulated by applying the Cholesky decomposition techniques based on auto- and cross-spectra of waves at pontoons. The wave spectral parameters can be determined with consideration of their long-term correlation while the coherence functions of wave elevations can be obtained by using phase-resolved methods. Based on the simulated wave elevations at each pontoon, the time series of first-order and second-order wave excitation forces are created by using the transfer functions and applied externally to each pontoon in the numerical model of the floating bridge. The proposed method is validated and applied to investigate the dynamic behavior of a floating bridge for the Bjørnafjord crossing as a case study. The inhomogeneous wave load effects are assessed by carrying out fully coupled time-domain simulations. It is found that the assumption of homogeneous wave conditions is conservative for the strong axis and weak axis bending moments, but significantly nonconservative for the axial force. The proposed method can also be applied for other very large floating structures subjected to the inhomogeneous wave field. Highlights: A generic method for evaluating inhomogeneous wave load effects of very long floating bridges. Both spatial variation and correlation of wave spectral parameters and coherence of wave elevations are considered. The method is demonstrated by a case study on a 5 km long floating bridge. The assumption of a homogeneous wave field might significantly underestimate the dynamic responses. The method is applicable for other floating structures subjected to inhomogeneous wave fields.